Prototype of Automatic Cover Roof Control system for Grain Drying Based on Internet of Things (IoT) - Putri, Dadva Pramesty Etsria; Yudhana, Anton (Signal and Image Processing Letters, 2020)
The sun is the largest source of heat energy on earth. Sunlight as an energy source can be used for the drying process in drying grain. Grain drying is done by drying in the open field or often referred to as traditional drying. Drying using sunlight has weaknesses, including if the weather changes, such as sudden rain, it will be difficult to move the grain. As a result, the dry grain becomes wet again so it takes more time to dry. From these problems, this research makes an automatic roof design when it rains, the roof will be closed automatically. If the weather is sunny and it is not raining, the roof will open. The sensors used are rain sensors and LDR sensors as light sensors that can produce several weather outputs such as sunny, cloudy and dark. While the material used is like a motor to be able to move the pulley. And the motor will move after getting instructions from the NodeMCU that the light received from the light sensor is in accordance with the command then the motor will move and the pulley will lift the light and strong plastic roof to be able to cover the roof perfectly after the rain sensor works. System testing shows an error in light of 5.5% while the system error shown at temperature is 0.01% and an error in humidity is 0.11%. The ability of the system to cover the roof when it is cloudy or when it is raining.